(untitled) (Scientific journal of the Fergana State University, 2026)
This article analyzes the lexical-semantic and grammatical features of the English legal texts, which today are considered the most prestigious and widespread legal means of communication internationally, in connection with culture, and touches on scientists and their works who have conducted research in this field. In the course of the study, the level of formality, the expression and cultural meaning of the language of English legal texts are studied based on the analysis of a systematic-functional grammatical, linguocultural and discursive approach.